Community Engagement in BUMDes PUJA BERSINAR Management Practices: Keterlibatan Komunitas dalam Praktik Pengelolaan BUMDes PUJA BERSINAR - Sulihan, Sulihan; Choiriyah, Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2024)
Background: This study explores the critical role of village-owned enterprises (BUMDes) in improving community welfare through effective management. Specific Background: It focuses on the management of BUMDes Puja Bersinar and the challenges it encounters. Knowledge Gap: There is limited understanding of the practical implementation of oversight frameworks in BUMDes, particularly regarding community involvement and transparency. Aims: The study aims to analyze the management practices and barriers of BUMDes Puja Bersinar. Results: Findings reveal that while oversight mechanisms exist, challenges such as insufficient internal audits and limited community engagement hinder effective management. Novelty: This research provides new insights into the operational dynamics of BUMDes, emphasizing the need for better participatory practices. Implications: Enhancing financial report transparency and establishing community feedback forums could significantly improve BUMDes management and promote sustainable community welfare outcomes. Highlights : Effective management of BUMDes is crucial for community welfare improvement. Challenges include inadequate internal audits and limited community participation. Enhancing transparency and feedback mechanisms can lead to better operational outcomes. Keywords: BUMDes, community welfare, management practices, transparency, oversight